Results-Based Financing to Promote Clean Stoves : Initial Lessons from Pilots in China and Indonesia - Zhang, Yabei (World Bank, Washington, DC, 2015)
Past market failures to deliver clean cooking and heating solutions, especially to low-income households, suggest the continued need for subsidies if universal access is to be achieved. To succeed, however, subsidies must be well-targeted, have low potential for “leakage,” and be calibrated to avoid destroying commercial incentives and discipline. Results-based financing, which disburses public resources against demonstrated results, can be used to mobilizeand sustain private-sector participation in scaling up access to clean stoves. Pilots implementing this approach under the World Banks Clean Stove Initiative show promising results.